Cachexia does not induce loss of myonuclei or muscle fibres during xenografted prostate cancer in mice. (16th November 2018) - Winje, Ivan Myhre; Sheng, Xia; Hansson, Kenth‐Arne; Solbrå, Andreas; Tennøe, Simen; Saatcioglu, Fahri; Bruusgaard, Jo Christiansen; Gundersen, Kristian
Abstract: Aim: Cachexia is a severe wasting disorder involving loss of body‐ and muscle mass reducing survival and quality of life in cancer patients. We aim at determining if cachexia is a mere perturbation of the protein balance or if the condition also involves a degenerative loss of myonuclei within the fibre syncytia or loss of whole muscle fibres. Methods: We induced cachexia by xenografting PC3 prostate cancer cells in nu/nu mice. Six weeks later, we counted myonuclei by in vivo microscopic imaging of single live fibres in the extensor digitorum longus muscle (EDL), and the EDL, soleus and tibialis anterior muscles were also harvested for ex vivo histology. Results: The mice lost on average 15% of the whole‐body wt. The muscle wet weight of the glycolytic, fast EDL was reduced by 14%, the tibialis anterior by 17%, and the slow, oxidative soleus by 6%. The fibre cross‐sectional area in the EDL was reduced by 21% with no loss of myonuclei or any significant reduction in the number of muscle fibres. TUNEL‐positive nuclei or fibres with embryonic myosin were rare both in cachectic and control muscles, and haematoxylin‐eosin staining revealed no clear signs of muscle pathology. Conclusion: The data suggest that the cachexia induced by xenografted prostate tumours induces a pronounced atrophy not accompanied by a loss of myonuclei or a loss of muscle fibres. Thus, stem cell related treatment might be redundant, and the quest for treatment options should rather focus on intervening with intracellular pathways regulating muscle fibre size.